Role of purinergic signalling in obesity-associated end-organ damage: focus on the effects of natural plant extracts - Che, Hangxiu; Wang, Yaqun; Lao, Jinhui; Deng, Yixin; Xu, Chirui; Yin, Hanxiao; Tang, Zheng; Huang, Yonghong; Xu, Hong (Frontiers in Endocrinology, 2023)
Obesity has become one of the major public health problems in both the developing and developed countries. Recent studies have suggested that the purinergic signalling is involved in obesity-associated end-organ damage through purine P1 and P2 receptors. In the search for new components for the treatments of obesity, we and other researchers have found much evidence that natural plant extracts may be promising novel therapeutic approaches by modulating purinergic signalling. In this review, we summarize a critical role of purinergic signalling in modulating obesity-associated end-organ damage, such as overhigh appetite, myocardial ischemia, inflammation, atherosclerosis, non-alcoholic fatty liver disease (NAFLD), hepatic steatosis and renal inflammation. Moreover, we focus on the potential roles of several natural plant extracts, including quercetin, resveratrol/trans-reseveratrol, caffeine, evodiamine and puerarin, in alleviating obesity-associated end-organ damage via purinergic signalling. We hope that the current knowledge of the potential roles of natural plant extracts in regulating purinergic signalling would provide new ideas for the treatment of obesity and obesity-associated end-organ damage.